CUIDADO NUTRICIONAL NO DIABETES NO PERÍODO GESTACIONAL: RELATO DE CASO - Teixeira, Beatriz Adriele Rocha; Amaral, Andrea Costa Morais; Oliveira, Alane Cabral Menezes de (Gep News, 2017)
Tipo de Apresentação: Pôster